Pengaruh Penambahan Pasta Tulang Ikan Lele dan Tepung Ampas Tahu Pada Kerupuk Lokal Terhadap Karakteristik Sensorinya - Faridah Handayasari; Intan Kusumaningrum; Raden Siti Nurlaela; Fiola Triyassari (JURNAL AGROINDUSTRI HALAL, 2025)
Crackers are snacks made from tapioca. This study aims to utilize catfish bones and tofu dregs flour as crackers. The research design used a one-factor Completely Randomized Design (CRD), with four treatment levels of the addition ratio: (0%: 0%), (15%: 15%), (20%: 10%), and (25%: 5%). The data analysis involved ANOVA with Duncan's Further Test, with a 95% confidence interval. The results showed that the sensory and hedonic properties of the crackers were significantly influenced by the color, aroma I (catfish bones), aroma II (tofu pulp flour), taste, texture, and overall experience. Additionally, increasing the concentration of tofu pulp flour led to a decrease in color, aroma, taste, and texture in the crackers. The selected product, A4 treatment crackers with the addition of 25% catfish bone paste and 5% tofu pulp flour, produces a brownish yellow color, aroma I towards not fishy, aroma II towards not languorous, taste towards salty, texture towards crispy. The hedonic results on all parameters lead to likes. The selected crackers had a moisture content of 5.41%, ash of 7.57%, protein of 5.40%, calcium of 3.801%, and physical test (chewability) of 465.34%.